PSYCHOSOCIAL PROGRAM INFLUENCES ON THE ACADEMIC ENGAGEMENT AMONG PALESTINIAN ORPHANS IN THE GAZA STRIP: A STUDY AT DAR AL ARQAM SCHOOL - Hamdaqa, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to highlight the influences of the psychosocial support program on the academic achievement among Palestinian orphans in the Gaza strip as evidence from Dar Al Arqam school. Two focus group discussion (FGD) were conducted with seven orphans to two groups from Dar Al Arqam school. The results pointed out the importance of programs in enhancing the emotional support and knowledge engagement for orphans through their had ability to enjoy the positive thinking about-facing their problems and the ability to think about the future. It also builds the relationship between the psychosocial program and the Academic achievement by increasing their academic engagement within the classroom. The research resulted in helping them to progress and achieve academic excellence and helped them to get rid of the trauma they faced during and after the war.